Pengaruh Penggunaan Medial Arch Support Terhadap Keseimbangan Dinamis Pada Kaki Pes Cavus Pada Orang Tua Lanjut Usia (LANSIA) - Muhammad Fathi; Cica Tri Mandasari Ningsih (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: According to The World Health Organization (WHO), in the Southeast Asia the Elderly population is 8% or around 142 million people. Feet function for shock absorber, Generally there are three types of foot structure, namely neutral or normal, flat foot, and cavus foot. The cavus foot will improve performance on the musculoskeletal structure to maintain postural stability and balance due to midfoothypomobile. As a result, cavus foot cannot distribute body weight evenly along the metatarsal heads and the lateral side of the foot, lowering the sensory plantar input and significantly the pressure on the foot is greater than the other foot postures. Method: The research design used was quasy experiment with cross sectional design. dynamic balance measurement with TUG test The study was conducted in April - July 2018 at the Posyandu at the elderly Klodran, Colomadu, Karanganyar. with a sample of 20 elderly. data collection using the wetfootprint pre test and post test with medial arch support. Results: the results of p value 0,000 <0,05 so that there is a difference in the dynamic balance in the elderly before and after being given Medial arch support. can also see from the mean acquisition value of the elderly before using the medial arch support of 13.7 while after using the medial arch support the mean gain of 13.2.Conclusion: the results of a study of 20 elderly people showed that dynamic balance in the legs of pes cavus in the elderly (elderly). before using the medial arch support higher than the dynamic balance at the foot of pes cavus in the elderly (elderly)